Superfine fiber color master batch and preparation method thereof
Patent Information
- Application Number
- CN202611477488.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-30
AI Technical Summary
在染色中,由于开纤后超细纤维的线密度低于0.2dtex,比表面积远远大于常规纤维,能够达到常规纤维的几十倍,从染浴中吸附染料的速度快,而且超细纤维的无定形区比较大,染料易扩散,所以表现出较高的上染速率,但是在染色中,尤其是染深色中,染料的用量大,大量的染料吸附在纤维的表面,水洗时产生大量浮色,造成污水污染,而且在染色中,还存在以下问题:
本发明通过改进色母粒的配方,能够提高色母粒中颜料的耐热性能,还能够保证在将得到的色母粒在与树脂切片混合后,得到的树脂切片色泽均匀,具体表现在色母粒不存在杂色粒、焦粒和黑点,在将色母粒应用于超细纤维后,颜料的保留率高;在进行纺丝时,可纺性好,具体表现在将色母粒与树脂切片混合后,压滤值低,为0.028-0.032MPa/g,当纺丝速度为1000m/min、1500m/min和2000m/min时,均不存在可纺性差的问题;在进行纺丝后,得到的超细纤维的强度高,柔软度好,得到的超细纤维的耐摩擦牢度和耐日晒牢度好,具体表现在超细纤维的断裂强度为2.6-3.6MPa,断裂伸长率为23.7-45.3%,断裂强度变异系数为4.5-6.4%,由超细纤维制备的麂皮绒的干摩擦牢度为5级,湿摩擦牢度为4-4.2级,耐光色牢度为7-7.4级,径向柔软度为6.0-6.5mm。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of color masterbatch technology, specifically to a color masterbatch for microfiber and its preparation method. Background Technology
[0002] In the preparation of suede fabric, island-island microfiber filaments are mainly used as raw materials. The process involves first weaving these filaments into a grey fabric, then subjecting it to pre-shrinking, alkali reduction, fiber opening, pre-forming, napping, brushing, and dyeing processes to obtain the suede fabric. The island component of the island-island microfiber is generally polyester or polyamide, while the sea component is generally polyethylene, polyamide, polypropylene, polyvinyl alcohol, polystyrene, and modified polyester, etc. The number of island components ranges from 16, 36, 64 to 200, and can even reach 900 or more. The ratio of sea component to island component has evolved from the original 60:40 to 20:80, and even reaches 10:90. In dyeing, because the linear density of microfiber after opening is less than 0.2 dtex and its specific surface area is much larger than that of conventional fibers, reaching tens of times that of conventional fibers, it adsorbs dye from the dye bath quickly. Moreover, the amorphous region of microfiber is relatively large, and the dye diffuses easily, thus exhibiting a high dyeing rate. However, in dyeing, especially in dark colors, a large amount of dye is used, and a large amount of dye is adsorbed on the surface of the fiber, producing a large amount of floating dye during washing, causing wastewater pollution. In addition, the following problems also exist in the dyeing process: Problem 1 is poor dyeing uniformity, specifically manifested in the following ways: microfibers have low linear density and large specific surface area, resulting in a fast dye adsorption rate and a tendency for uneven adsorption; the microstructure of some microfibers differs from that of conventional fibers, leading to inherently poor dyeing uniformity; the cross-sections of microfibers are mostly irregular in shape, and their surfaces are not smooth enough, which not only further increases the specific surface area but also accelerates the adsorption of dyes, making it difficult to achieve uniform dyeing; the low linear density of microfibers makes them more sensitive to physical and chemical reactions than conventional fibers, and unevenness in the alkali reduction and pre-forming processes can lead to uneven dyeing. Problem 2 is poor dyeing depth, which is specifically manifested in the fact that the diameter of microfiber is very small, and the diffuse reflection of light on the fabric surface is enhanced. Therefore, the apparent color tone is correspondingly weakened. To obtain the same dyeing depth, the dye concentration required for microfiber is much higher than that for ordinary fiber. Problem 3 is poor color fastness, specifically manifested in the following ways: microfiber has a large specific surface area and irregular cross-section, making it easy to be stained with dyes and difficult to wash off, resulting in poor rubbing fastness; microfiber has a high polymer content, making it easy to adsorb dyes under humid and hot conditions, resulting in poor wet fastness; microfiber has a low linear density and a large specific surface area, making it easy for light and gas to enter the fiber, resulting in poor light fastness.
[0003] In summary, to address the aforementioned issues, Xu Hua et al., in their paper "Development of Carbon Black Island-Sea Ultrafine Filaments" (Synthetic Fibers, 2019), disclosed the addition of carbon black polyester masterbatch to polyester chips as the island phase of island-sea fibers for spinning. This improves color fastness, reduces wastewater pollution, and enhances dyeing depth without or with minimal dye use. However, the paper also revealed that due to the fineness of the island component's monofilaments, the carbon black powder used in the black polyester masterbatch for spinning requires a high fineness, typically 10-20 nm. However, the smaller the carbon black powder particle size, the more difficult it is to disperse, resulting in poorer even dyeing properties in the suede fabric. To solve this problem, the paper employed two methods: multiple compounding granulation and shear-coagulation granulation. A comparison of these two methods revealed that multiple compounding granulation is more complex and cumbersome, and the carbon black powder is prone to agglomeration during mixing, easily leading to color differences and affecting the uniformity of the polyester chip color. The principle of shear-blending granulation is to mix carbon black powder and polyester chips at high speed, dry and shear-blend them, and then extrude, granulate and dry them. Although shear-blending granulation can fully mix carbon black powder and polyester chips, resulting in polyester chips with uniform color, saving time for the second compound granulation and improving production efficiency, it has high equipment requirements. Furthermore, Yang Yunmin et al. disclosed in "Advances in Pre-spinning Coloring Technology of Polyester Fibers" (Synthetic Fiber Industry, 2008) and Yu Xiaocheng et al. in "Discussion on Methods to Improve the Rubbing Color Fastness of Indeterminate Island-type Fiber Synthetic Leather" (China Leather, 2010) that when using masterbatch for pre-spinning dyeing, dyes with low heat resistance are not suitable for polyester with high spinning temperature, and it will also have a certain impact on the strength and softness of microfiber.
[0004] To address the aforementioned issues, the applicant reviewed relevant literature on improving the heat resistance of dyes and enhancing the strength and softness of microfibers. The applicant found that Chen Kan et al. in "Application Research of Diatomite in Polyolefin Masterbatch" (Engineering Plastics Application, 2015), Gao Xuqian et al. in "The Influence of Different Dispersants on PET Fiber Blue Masterbatch" (Engineering Plastics Application, 2019), Li Wenxiao et al. in "The Influence of Pigment Modification on the Filterability of Masterbatch" (Dyes and Dyeing, 2018), and Yu Xiaocheng et al. in "Discussion on Methods to Improve the Color Fastness to Rubbing of Indeterminate Island-Type Fiber Synthetic Leather" (China Leather, 2010) respectively disclosed methods for improving the dispersibility and heat resistance of pigments in masterbatches using diatomite, improving the dispersibility of pigments in masterbatches using modified waxes, polyethylene waxes, and olefin elastomers, improving the dispersibility of pigments in masterbatches using polymeric auxiliaries, and improving the softness of microfibers using a rubbing process. However, the solutions presented in the aforementioned literature still have the following problems: The first issue concerns the spinnability of microfibers. Chen Xiumiao et al., in their paper "Research on the Preparation of Textile Fibers from Diatomite" (Shanghai Textile Science and Technology, 2019), disclosed that mixing diatomite-containing masterbatch with PET chips affects the spinnability of PET, specifically manifesting as difficulties in spinning and increased yarn breakage. Furthermore, considering the fineness of microfiber monofilaments, the fineness requirements for diatomite are high. During wet ultrafine grinding and drying of diatomite, it is prone to agglomeration, and when added to color masterbatch, the small particle size also presents dispersion difficulties.
[0005] The second issue is the still relatively low strength of microfibers. Gao Xuqian et al., in their paper "The Influence of Different Dispersants on Blue Masterbatch of PET Fibers" (Engineering Plastics Application, 2019), disclosed that compared to pure PET, the breaking strength of PET colored filaments decreased but the elongation at break increased without dispersants. This is because the addition of pigments has a heterogeneous nucleation effect. Compared to colored filaments without dispersants, the non-polar dispersant polyethylene wax did not provide good wetting for the pigments, and pigment agglomerates created defects within the PET fibers. Therefore, when non-polar dispersant polyethylene wax was added, both the breaking strength and elongation at break of the PET colored filaments decreased. However, when polar dispersant modified wax and non-polar dispersant olefin elastomer were added, the breaking strength remained unchanged compared to PET colored filaments without dispersants. This indicates that simply improving the dispersibility of pigments cannot solve the problem of low strength in microfibers.
[0006] The third issue is the softness of microfiber. Although the texturing process can improve the softness of microfiber, the improvement is limited and it leads to a more complex preparation method. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a color masterbatch for microfiber and its preparation method. By improving the formulation of the color masterbatch, this invention enhances the heat resistance of the pigments in the masterbatch and ensures that the obtained color masterbatch has uniform color after being mixed with resin chips. It also ensures good spinnability during spinning, and the resulting microfiber has high strength, good softness, and good rubbing fastness and light fastness, thus enabling it to be better applied in the field of new energy vehicle interiors.
[0008] To solve the above technical problems, the technical solution adopted by the present invention is as follows: A masterbatch for microfiber, by weight, is composed of the following raw materials: 60-80 parts matrix resin, 20-40 parts pigment mixture, 3-3.5 parts dispersant, 0.3-0.5 parts composite zinc oxide, and 0.3-0.5 parts antioxidant; The matrix resin is polyester chips or polyamide chips; Preferably, the matrix resin is polyester chips or polyamide 6 chips; More preferably, the intrinsic viscosity of the polyester chips is 0.5-1 dL / g; More preferably, the intrinsic viscosity of the polyamide 6 chips is 2-3 dL / g; The matrix resin is a dried matrix resin with a moisture content ≤100ppm. Preferably, the moisture content of the matrix resin is controlled by drying, specifically drying at 120-130℃ for 10-30 hours. The dispersant is polyethylene wax; Preferably, the dispersant is polyethylene wax, and the molecular weight of the polyethylene wax is 2000-3000; The antioxidant is one or a combination of antioxidant 1010, antioxidant 1076, and antioxidant 618; The pigment mixture is prepared by the following method: pigment is mixed with water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone, subjected to a first reflux stirring at 80-85°C, and spray-dried to obtain a dispersed pigment; silica is mixed with water, low molecular weight polyethylene glycol, and zinc stearate, subjected to a second reflux stirring at 85-90°C, and spray-dried to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed and stirred at room temperature to obtain the pigment mixture. Preferably, in the method for preparing the pigment mixture, the particle size of the pigment is 10-20 nm; Preferably, in the method for preparing the pigment mixture, the mass ratio of pigment to water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone is 100:500-600:5-6:5-6. Preferably, in the method for preparing the pigment mixture, when the first reflux stirring is performed at 80-85°C, the stirring speed is 300-500 rpm and the stirring time is 60-90 min. Preferably, in the preparation method of the pigment mixture, the inlet air temperature is 170-190℃ during spray drying; Preferably, in the method for preparing the pigment mixture, the mass ratio of silica to water, low molecular weight polyethylene glycol, and zinc stearate is 100:500-600:5-6:5-6; Preferably, in the preparation method of the pigment mixture, when the second reflux stirring is performed at 85-90°C, the stirring speed is 300-500 rpm and the stirring time is 90-120 min; Preferably, in the method for preparing the pigment mixture, the mass ratio of dispersed pigment to dispersed silica is 9-11:1; Preferably, in the method for preparing the pigment mixture, when stirring at room temperature, the stirring speed is 300-500 rpm and the stirring time is 30-60 min; Preferably, in the method for preparing the pigment mixture, the pigment is one of carbon black, pigment red 214, pigment yellow 191, pigment purple 23, pigment blue 15:3, and pigment green 7; Preferably, in the method for preparing the pigment mixture, the high molecular weight polyethylene glycol has a molecular weight of 4000 or 6000; Preferably, in the method for preparing the pigment mixture, the polyvinylpyrrolidone is polyvinylpyrrolidone K30 or polyvinylpyrrolidone K60. Preferably, in the method for preparing the pigment mixture, the silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; Preferably, in the method for preparing the pigment mixture, the low molecular weight polyethylene glycol has a molecular weight of 400 or 600. The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol, ball milled and spray dried to obtain composite zinc oxide. Preferably, in the preparation method of the composite zinc oxide, the mass ratio of nano zinc oxide to water, high molecular weight polyethylene glycol, and low molecular weight polyethylene glycol is 100:400-450:5-6:5-6. Preferably, in the method for preparing the composite zinc oxide, during ball milling, zirconium oxide grinding balls with a particle size of 0.8-1.2 mm are used, the ball-to-material ratio is 5-10:1, the ball milling speed is 900-1100 rpm, and the ball milling time is 50-70 min. Preferably, in the preparation method of the composite zinc oxide, the inlet air temperature during spray drying is 170-190℃; Preferably, in the preparation method of the composite zinc oxide, the particle size of the nano zinc oxide is 10-20 nm; Preferably, in the method for preparing the composite zinc oxide, the molecular weight of the high molecular weight polyethylene glycol is 4000 or 6000; Preferably, in the method for preparing the composite zinc oxide, the low molecular weight polyethylene glycol has a molecular weight of 400 or 600. A aforementioned masterbatch is prepared by the following method: weighing the matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight parts, mixing at high speed, drying, melt extrusion, cooling, pelletizing, and drying to obtain the masterbatch; Preferably, in the method for preparing the color masterbatch, the high-speed mixing speed is 900-1100 rpm and the high-speed mixing time is 10-20 min. Preferably, in the method for preparing the color masterbatch, the drying rate is 165-175℃ and the drying time is 10-20 min. Preferably, in the method for preparing the color masterbatch, the melting temperature during melt extrusion is 260-285℃; Preferably, in the preparation method of the color masterbatch, the drying temperature is 110-120℃.
[0009] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention improves the heat resistance of pigments in masterbatches by modifying the masterbatch formulation. It also ensures that the resulting resin chips have uniform color after mixing with the masterbatch, specifically by eliminating discolored particles, burnt particles, and black spots. Furthermore, the masterbatch exhibits high pigment retention when applied to microfibers. During spinning, it demonstrates good spinnability, specifically by exhibiting a low filtration pressure value (0.028-0.032 MPa / g) after mixing with resin chips, even at spinning speeds of 1000 m / min, 1500 m / min, and 2000 m / min. At speeds of 00 m / min, there are no issues with poor spinnability. After spinning, the resulting microfibers exhibit high strength and good softness, as well as good rubbing fastness and light fastness. Specifically, the microfibers have a breaking strength of 2.6-3.6 MPa, a breaking elongation of 23.7-45.3%, and a breaking strength coefficient of variation of 4.5-6.4%. The suede made from microfibers has a dry rubbing fastness of grade 5, a wet rubbing fastness of grade 4-4.2, a light fastness of grade 7-7.4, and a radial softness of 6.0-6.5 mm. Detailed Implementation
[0010] To provide a clearer understanding of the technical features, objectives, and effects of the present invention, specific embodiments of the present invention are now described.
[0011] In the examples and comparative examples, the moisture content of the dried matrix resin is required to be ≤100ppm.
[0012] Example 1 This embodiment provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.3 parts of composite zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1010; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 10 nm, then mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:500:5:5, refluxed at 80°C (stirring speed 300 rpm) for 60 min, and spray-dried (inlet air temperature 170°C) to obtain a dispersed pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:500:5:5, refluxed at 85°C (stirring speed 300 rpm) for 90 min, and spray-dried (inlet air temperature 170°C) to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed in a mass ratio of 9:1 and stirred at room temperature (stirring speed 300 rpm) for 30 min to obtain the pigment mixture; In the pigment mixture, the pigment is carbon black; The high molecular weight polyethylene glycol has a molecular weight of 4000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K30. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:400:5:5, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 5:1, and a ball milling speed of 1000 rpm) for 50 min, and spray-dried (inlet air temperature of 170℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 10 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000; The low molecular weight polyethylene glycol has a molecular weight of 400.
[0013] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0014] Example 2 This embodiment is based on Example 1, but with adjustments to the weight proportions of each raw material in the color masterbatch.
[0015] This embodiment provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 80 parts of dried matrix resin, 40 parts of pigment mixture, 3.5 parts of dispersant, 0.5 parts of composite zinc oxide, and 0.5 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1010; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 10 nm, then mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:500:5:5, refluxed at 80°C (stirring speed 300 rpm) for 60 min, and spray-dried (inlet air temperature 170°C) to obtain a dispersed pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:500:5:5, refluxed at 85°C (stirring speed 300 rpm) for 90 min, and spray-dried (inlet air temperature 170°C) to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed in a mass ratio of 9:1 and stirred at room temperature (stirring speed 300 rpm) for 30 min to obtain the pigment mixture; In the pigment mixture, the pigment is carbon black; The high molecular weight polyethylene glycol has a molecular weight of 4000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K30. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:400:5:5, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 5:1, and a ball milling speed of 1000 rpm) for 50 min, and spray-dried (inlet air temperature of 170℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 10 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000; The low molecular weight polyethylene glycol has a molecular weight of 400.
[0016] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0017] Example 3 This embodiment is based on Example 1, but with adjustments to the amount and parameters of each raw material in the preparation method of the pigment mixture.
[0018] This embodiment provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.3 parts of composite zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1010; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 20 nm, then mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:600:6:6, refluxed at 85°C (stirring speed 500 rpm) for 90 min, and spray-dried (inlet air temperature 190°C) to obtain a dispersed pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:600:6:6, refluxed at 90°C (stirring speed 500 rpm) for 120 min, and spray-dried (inlet air temperature 190°C) to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed in a mass ratio of 11:1 and stirred at room temperature (stirring speed 500 rpm) for 60 min to obtain the pigment mixture; In the pigment mixture, the pigment is carbon black; The high molecular weight polyethylene glycol has a molecular weight of 6000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K60. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 600; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:400:5:5, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 5:1, and a ball milling speed of 1000 rpm) for 50 min, and spray-dried (inlet air temperature of 170℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 10 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000; The low molecular weight polyethylene glycol has a molecular weight of 400.
[0019] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0020] Example 4 This embodiment is based on Example 1, but with adjustments to the amount and parameters of each raw material in the preparation method of composite zinc oxide.
[0021] This embodiment provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.3 parts of composite zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1010; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 10 nm, then mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:500:5:5, refluxed at 80°C (stirring speed 300 rpm) for 60 min, and spray-dried (inlet air temperature 170°C) to obtain a dispersed pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:500:5:5, refluxed at 85°C (stirring speed 300 rpm) for 90 min, and spray-dried (inlet air temperature 170°C) to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed in a mass ratio of 9:1 and stirred at room temperature (stirring speed 300 rpm) for 30 min to obtain the pigment mixture; In the pigment mixture, the pigment is carbon black; The high molecular weight polyethylene glycol has a molecular weight of 4000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K30. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:450:6:6, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 10:1, and a ball milling speed of 1000 rpm) for 70 min, and spray-dried (inlet air temperature of 190℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 20 nm; The high molecular weight polyethylene glycol has a molecular weight of 6000; The low molecular weight polyethylene glycol has a molecular weight of 600.
[0022] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0023] Example 5 This embodiment is based on Example 1, but with adjustments made to the type of dry matrix resin.
[0024] This embodiment provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.3 parts of composite zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyamide 6 chips, and the intrinsic viscosity of the polyamide 6 chips is 2.7 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1010; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 10 nm, then mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:500:5:5, refluxed at 80°C (stirring speed 300 rpm) for 60 min, and spray-dried (inlet air temperature 170°C) to obtain a dispersed pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:500:5:5, refluxed at 85°C (stirring speed 300 rpm) for 90 min, and spray-dried (inlet air temperature 170°C) to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed in a mass ratio of 9:1 and stirred at room temperature (stirring speed 300 rpm) for 30 min to obtain the pigment mixture; In the pigment mixture, the pigment is carbon black; The high molecular weight polyethylene glycol has a molecular weight of 4000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K30. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:400:5:5, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 5:1, and a ball milling speed of 1000 rpm) for 50 min, and spray-dried (inlet air temperature of 170℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 10 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000; The low molecular weight polyethylene glycol has a molecular weight of 400.
[0025] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0026] Example 6 This embodiment is based on Example 1, but with adjustments made to the types of pigments in the pigment composition.
[0027] This embodiment provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.3 parts of composite zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1010; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 10 nm, then mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:500:5:5, refluxed at 80°C (stirring speed 300 rpm) for 60 min, and spray-dried (inlet air temperature 170°C) to obtain a dispersed pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:500:5:5, refluxed at 85°C (stirring speed 300 rpm) for 90 min, and spray-dried (inlet air temperature 170°C) to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed in a mass ratio of 9:1 and stirred at room temperature (stirring speed 300 rpm) for 30 min to obtain the pigment mixture; In the pigment mixture, the pigment is Pigment Red 214; The high molecular weight polyethylene glycol has a molecular weight of 4000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K30. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:400:5:5, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 5:1, and a ball milling speed of 1000 rpm) for 50 min, and spray-dried (inlet air temperature of 170℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 10 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000; The low molecular weight polyethylene glycol has a molecular weight of 400.
[0028] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0029] Example 7 This embodiment is based on Example 1, but with adjustments made to the types of pigments in the pigment composition.
[0030] This embodiment provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.3 parts of composite zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1010; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 10 nm, then mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:500:5:5, refluxed at 80°C (stirring speed 300 rpm) for 60 min, and spray-dried (inlet air temperature 170°C) to obtain a dispersed pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:500:5:5, refluxed at 85°C (stirring speed 300 rpm) for 90 min, and spray-dried (inlet air temperature 170°C) to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed in a mass ratio of 9:1 and stirred at room temperature (stirring speed 300 rpm) for 30 min to obtain the pigment mixture; In the pigment mixture, the pigment is Pigment Yellow 191; The high molecular weight polyethylene glycol has a molecular weight of 4000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K30. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:400:5:5, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 5:1, and a ball milling speed of 1000 rpm) for 50 min, and spray-dried (inlet air temperature of 170℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 10 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000; The low molecular weight polyethylene glycol has a molecular weight of 400.
[0031] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0032] Example 8 This embodiment is based on Example 1, but with adjustments made to the types of pigments in the pigment composition.
[0033] This embodiment provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.3 parts of composite zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1010; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 10 nm, then mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:500:5:5, refluxed at 80°C (stirring speed 300 rpm) for 60 min, and spray-dried (inlet air temperature 170°C) to obtain a dispersed pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:500:5:5, refluxed at 85°C (stirring speed 300 rpm) for 90 min, and spray-dried (inlet air temperature 170°C) to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed in a mass ratio of 9:1 and stirred at room temperature (stirring speed 300 rpm) for 30 min to obtain the pigment mixture; In the pigment mixture, the pigment is pigment violet 23; The high molecular weight polyethylene glycol has a molecular weight of 4000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K30. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:400:5:5, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 5:1, and a ball milling speed of 1000 rpm) for 50 min, and spray-dried (inlet air temperature of 170℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 10 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000; The low molecular weight polyethylene glycol has a molecular weight of 400.
[0034] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0035] Example 9 This embodiment is based on Example 1, but with adjustments made to the types of pigments in the pigment composition.
[0036] This embodiment provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.3 parts of composite zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1010; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 10 nm, then mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:500:5:5, refluxed at 80°C (stirring speed 300 rpm) for 60 min, and spray-dried (inlet air temperature 170°C) to obtain a dispersed pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:500:5:5, refluxed at 85°C (stirring speed 300 rpm) for 90 min, and spray-dried (inlet air temperature 170°C) to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed in a mass ratio of 9:1 and stirred at room temperature (stirring speed 300 rpm) for 30 min to obtain the pigment mixture; In the pigment mixture, the pigment is pigment blue in a 15:3 ratio; The high molecular weight polyethylene glycol has a molecular weight of 4000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K30. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:400:5:5, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 5:1, and a ball milling speed of 1000 rpm) for 50 min, and spray-dried (inlet air temperature of 170℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 10 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000; The low molecular weight polyethylene glycol has a molecular weight of 400.
[0037] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0038] Example 10 This embodiment is based on Example 1, but with adjustments made to the types of pigments in the pigment composition.
[0039] This embodiment provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.3 parts of composite zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1010; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 10 nm, then mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:500:5:5, refluxed at 80°C (stirring speed 300 rpm) for 60 min, and spray-dried (inlet air temperature 170°C) to obtain a dispersed pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:500:5:5, refluxed at 85°C (stirring speed 300 rpm) for 90 min, and spray-dried (inlet air temperature 170°C) to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed in a mass ratio of 9:1 and stirred at room temperature (stirring speed 300 rpm) for 30 min to obtain the pigment mixture; In the pigment mixture, the pigment is pigment green 7; The high molecular weight polyethylene glycol has a molecular weight of 4000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K30. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:400:5:5, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 5:1, and a ball milling speed of 1000 rpm) for 50 min, and spray-dried (inlet air temperature of 170℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 10 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000; The low molecular weight polyethylene glycol has a molecular weight of 400.
[0040] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0041] Example 11 This embodiment is based on Example 1, but with adjustments made to the type of antioxidant.
[0042] This embodiment provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.3 parts of composite zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1076; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 10 nm, then mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:500:5:5, refluxed at 80°C (stirring speed 300 rpm) for 60 min, and spray-dried (inlet air temperature 170°C) to obtain a dispersed pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:500:5:5, refluxed at 85°C (stirring speed 300 rpm) for 90 min, and spray-dried (inlet air temperature 170°C) to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed in a mass ratio of 9:1 and stirred at room temperature (stirring speed 300 rpm) for 30 min to obtain the pigment mixture; In the pigment mixture, the pigment is carbon black; The high molecular weight polyethylene glycol has a molecular weight of 4000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K30. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:400:5:5, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 5:1, and a ball milling speed of 1000 rpm) for 50 min, and spray-dried (inlet air temperature of 170℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 10 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000; The low molecular weight polyethylene glycol has a molecular weight of 400.
[0043] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0044] Example 12 This embodiment is based on Example 1, but with adjustments made to the type of antioxidant.
[0045] This embodiment provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.3 parts of composite zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 618; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 10 nm, then mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:500:5:5, refluxed at 80°C (stirring speed 300 rpm) for 60 min, and spray-dried (inlet air temperature 170°C) to obtain a dispersed pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:500:5:5, refluxed at 85°C (stirring speed 300 rpm) for 90 min, and spray-dried (inlet air temperature 170°C) to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed in a mass ratio of 9:1 and stirred at room temperature (stirring speed 300 rpm) for 30 min to obtain the pigment mixture; In the pigment mixture, the pigment is carbon black; The high molecular weight polyethylene glycol has a molecular weight of 4000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K30. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:400:5:5, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 5:1, and a ball milling speed of 1000 rpm) for 50 min, and spray-dried (inlet air temperature of 170℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 10 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000; The low molecular weight polyethylene glycol has a molecular weight of 400.
[0046] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0047] Comparative Example 1 This comparative example is based on Example 1, but with adjustments made to the preparation method of the pigment mixture.
[0048] This comparative example provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.3 parts of composite zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1010; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 10 nm to obtain the ground pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:500:5:5, refluxed and stirred at 85°C (stirring speed 300 rpm) for 90 min, and then spray-dried (inlet air temperature 170°C) to obtain dispersed silica; the ground pigment is mixed with the dispersed silica in a mass ratio of 8.2:1, and stirred at room temperature (stirring speed 300 rpm) for 30 min to obtain the pigment mixture; In the pigment mixture, the pigment is carbon black; The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:400:5:5, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 5:1, and a ball milling speed of 1000 rpm) for 50 min, and spray-dried (inlet air temperature of 170℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 10 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000; The low molecular weight polyethylene glycol has a molecular weight of 400.
[0049] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0050] Comparative Example 2 This comparative example is based on Example 1, but with adjustments made to the preparation method of the pigment mixture.
[0051] This comparative example provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.3 parts of composite zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1010; The pigment mixture is prepared by the following method: the pigment is ground to a particle size of 10 nm, then the pigment is mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:500:5:5, refluxed and stirred at 80°C (stirring speed of 300 rpm) for 60 min, and spray dried (inlet air temperature of 170°C) to obtain a dispersed pigment; the dispersed pigment is mixed with silica in a mass ratio of 9:0.91 and stirred at room temperature (stirring speed of 300 rpm) for 30 min to obtain the pigment mixture. In the pigment mixture, the pigment is carbon black; The high molecular weight polyethylene glycol has a molecular weight of 4000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K30. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with deionized water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol in a mass ratio of 100:400:5:5, ball-milled (using zirconia grinding balls with a particle size of 1 mm, a ball-to-material ratio of 5:1, and a ball milling speed of 1000 rpm) for 50 min, and spray-dried (inlet air temperature of 170℃) to obtain composite zinc oxide; In the composite zinc oxide, the particle size of the nano zinc oxide is 10 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000; The low molecular weight polyethylene glycol has a molecular weight of 400.
[0052] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0053] Comparative Example 3 This comparative example is based on Example 1, but with the composite zinc oxide replaced by nano zinc oxide.
[0054] This comparative example provides a color masterbatch for microfiber, which, by weight, is composed of the following raw materials: 60 parts of dried matrix resin, 20 parts of pigment mixture, 3 parts of dispersant, 0.27 parts of nano zinc oxide, and 0.3 parts of antioxidant. The dried matrix resin is dried polyester chips, and the intrinsic viscosity of the polyester chips is 0.68 dL / g; The drying method for the dried matrix resin is to dry it at 120°C for 20 hours; The dispersant is polyethylene wax with a molecular weight of 2000; The antioxidant is antioxidant 1010; The pigment mixture is prepared by the following method: The pigment is ground to a particle size of 10 nm, then mixed with deionized water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone in a mass ratio of 100:500:5:5, refluxed at 80°C (stirring speed 300 rpm) for 60 min, and spray-dried (inlet air temperature 170°C) to obtain a dispersed pigment; silica is mixed with deionized water, low molecular weight polyethylene glycol, and zinc stearate in a mass ratio of 100:500:5:5, refluxed at 85°C (stirring speed 300 rpm) for 90 min, and spray-dried (inlet air temperature 170°C) to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed in a mass ratio of 9:1 and stirred at room temperature (stirring speed 300 rpm) for 30 min to obtain the pigment mixture; In the pigment mixture, the pigment is carbon black; The high molecular weight polyethylene glycol has a molecular weight of 4000; The polyvinylpyrrolidone is designated as polyvinylpyrrolidone K30. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400; The nano zinc oxide has a particle size of 10 nm.
[0055] The aforementioned masterbatch for microfiber is prepared by the following method: Weigh the dry matrix resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, add them all to a high-speed mixer, mix (mixing speed is 1000 rpm) for 10 min, transfer to a granulator, dry (drying speed is 165℃) for 10 min, melt extrude (melting temperature is 260℃), cool in a water bath, granulate, and dry (drying temperature is 110℃) to obtain the masterbatch.
[0056] Application Example 1 This application example illustrates the method of using the color masterbatches from Examples 1-4, 6-12, and Comparative Examples 1-3 in the preparation of ultrafine fibers, specifically as follows: The color masterbatch and resin chips were mixed evenly, with the addition mass of the color masterbatch being 28% of the resin chips, as the island phase component. The island phase component, which had been pre-crystallized (pre-crystallization temperature was 135℃) and dried (drying temperature was 160℃), was mixed with the sea phase component, which had been pre-crystallized and dried, at a mass ratio of 70:30 and spun at a spinning temperature of 290℃. The mixture was then shaped by side blowing to obtain island-island ultrafine fibers with an average diameter of 3.12μm and a single fiber linear density of 0.086dtex. The marine phase component is alkali-soluble polyester chips with an intrinsic viscosity of 0.67 dL / g.
[0057] Application Example 2 This application example illustrates the method of using the color masterbatch from Example 5 in the preparation of ultrafine fibers, specifically as follows: The color masterbatch and resin chips were mixed evenly, with the addition mass of the color masterbatch being 28% of the resin chips, as the island phase component. The island phase component, which had been pre-crystallized (pre-crystallization temperature was 135℃) and dried (drying temperature was 90℃), was mixed with the dried sea phase component at a mass ratio of 70:30 and spun at a spinning temperature of 278℃. The spinning was performed by side blowing to obtain island-island ultrafine fibers with an average diameter of 3.1μm and a single fiber linear density of 0.086dtex. The marine component is low-density polyethylene, and the melt flow index of low-density polyethylene at 190°C and 2.16 kg is 50 g / 10 min.
[0058] Test case 1. Observe whether the color masterbatches obtained in Examples 1-12 and Comparative Examples 1-3 have uniform color. During observation, take a handful of color masterbatches and visually inspect them under natural light for the presence of discolored particles, burnt particles, and black spots. The visual inspection results are shown in Table 1: Table 1
[0059] 2. Referring to HG / T 4768.5-2014 "Evaluation of dispersibility in pigments and extender pigments in plastics - Part 5: Determination of colorant dispersibility by heated melt extrusion method", the filter press values of the masterbatches obtained in Examples 1-12 and Comparative Examples 1-3 were tested. The test method was as follows: Heating the single-screw extruder (length-to-diameter ratio 20, diameter 25mm) and cleaning the inside and screw of the extruder are performed. A filter screen (1400 mesh) is installed. The extruder is started, and the mixture (i.e., the island phase component corresponding to Application Examples 1 and 2) is added. When the melt temperature is stable and the pressure remains constant, the pressure value P0 is recorded. Extrusion begins (pump rate 50cm). 3 The pressure is recorded every 5 minutes for 60 minutes, with the maximum observed pressure value P2 recorded during the test. If the pressure reaches 8 MPa during the test, the test is stopped. The pressure filtration value is calculated using the following formula: Filtration value = (P2 - P0) / m; (m is the amount of colorant used in the test) The calculation results are shown in Table 2 (each sample was tested 10 times, and the average value was taken): Table 2
[0060] 3. When preparing island-shaped microfibers using the masterbatches of Examples 1-12 and Comparative Examples 1-3 according to the methods of Application Examples 1 and 2, different spinning speeds (1000 m / min, 1500 m / min, and 2000 m / min) were set during the mixed spinning process, and the spinning temperature and component pressure were kept consistent. The results were recorded to determine whether poor spinnability (difficulty spinning, increased breakage, difficulty winding) occurred at different spinning speeds. The results are shown in Table 3. Table 3
[0061] 4. Following the methods of Application Examples 1 and 2, and using the masterbatches of Examples 1-12 and Comparative Examples 1-3 to prepare island-of-the-sea microfibers respectively, the breaking strength, elongation at break, and coefficient of variation of breaking strength of the obtained island-of-the-sea microfibers were tested. For the breaking strength and elongation at break tests, the test standard GB / T 14337-2022 was followed. Breaking strength was defined as the ratio of fiber tensile breaking strength to fineness, the tensile speed was 40 mm / min, and the spacing was 20 mm. The test results are shown in Table 4 (each sample was tested 25 times, and the average value was taken): Table 4
[0062] 5. Following the methods of Application Examples 1 and 2, after preparing island-of-the-sea microfiber using the masterbatches of Examples 1-12 and Comparative Examples 1-3 respectively, the island-of-the-sea microfiber was used as warp yarn and 165dtex / 48F polyester DTY as weft yarn for weaving (warp density of 790 ends / 10cm, weft density of 350 ends / 10cm) to obtain a grey fabric. This fabric was then pre-shrinked, subjected to alkali reduction, fiber opening, pre-forming, napping, and brushing to obtain a suede fabric. The dry rubbing fastness and wet rubbing fastness were then tested (the test methods for dry rubbing fastness and wet rubbing fastness refer to GB / T 3920-2008 "Textiles - Tests for Color Fastness - Color Fastness to Rubbing", and the rating method refers to GB / T...). The following tests were conducted: 251-2008 "Grey Chart for the Assessment of Staining"; light fastness (the test method for light fastness is based on GB / T8427-2019 "Textiles - Tests for Color Fastness - Color Fastness to Artificial Light: Xenon Arc", test method 1); and radial softness (the test method is based on ISO 17235:2002 | IULTCS / IUP 36 "Leather - Physical and Mechanical Tests - Determination of Softness"). The test results are shown in Table 5 (each sample was tested 10 times, and the average value was taken). Table 5
[0063] 5. In Comparative Examples 1-3, the pigments in the pigment compositions were all replaced with an equal mass of Pigment Blue in a 15:3 ratio. Then, the microfibers were prepared using the same method as in Application Example 1, along with the masterbatch from Example 9. The microfibers were then used as warp yarns, and 165 dtex / 48F polyester DTY was used as weft yarns for weaving (warp density 790 ends / 10cm, weft density 350 ends / 10cm) to obtain a grey fabric. This fabric underwent pre-shrinking, alkali reduction, fiber opening, pre-forming, napping, and brushing to obtain suede fabric. Following the method disclosed by Chen Kan et al. in "Application Research of Diatomaceous Earth in Polyolefin Masterbatch" (Engineering Plastics Application, 2015), the coloring performance was tested. Specifically, the b-value and reflectance at 450 nm of the obtained suede fabric were tested. The test results are shown in Table 6 (each sample was tested 10 times, and the average value was taken). Table 6
[0064] As shown in Tables 1-6, compared with Example 1, the masterbatches of Comparative Examples 1-3 all exhibit high filtration pressure values (caused by uneven pigment dispersion), which affects the breaking strength, elongation at break, and coefficient of variation of breaking strength of microfibers. This, in turn, affects the dry rubbing fastness, wet rubbing fastness, light fastness, radial softness, and dyeing performance of suede made from microfibers. Furthermore, the masterbatches of Comparative Examples 1 and 3 also contain discolored particles, burnt particles, and black spots, which affect the spinnability of microfibers. This indicates that the preparation methods of the pigment mixture and the composite zinc oxide have a certain improving effect on the dispersion of pigments in the masterbatch, as well as the strength, color fastness, softness, dyeing performance, and spinnability of the prepared microfibers.
[0065] In Examples 1-12, the pigment mixture was prepared by mixing the pigment with high molecular weight polyethylene glycol and polyvinylpyrrolidone, followed by stirring and spray drying. The dispersing ability of high molecular weight polyethylene glycol and polyvinylpyrrolidone reduced pigment agglomeration, and the high molecular weight polyethylene glycol and polyvinylpyrrolidone reduced the contact between the pigment and the polyester / polyamide, thereby reducing the heterogeneous nucleation effect of the pigment. Furthermore, Jin Guidong et al., in "Study on Chain Motion of PEG / PVP System by Spin Labeling Method" (Journal of Spectroscopy, 2001), disclosed that the hydroxyl groups at the ends of the polyethylene glycol chain and the carbonyl groups on the side chains of polyvinylpyrrolidone can interact... Hydrogen bonds can be formed, and the hydrogen bonding effect is greatly affected by the molecular weight of polyethylene glycol. Low molecular weight polyethylene glycol has more hydroxyl groups, which have a stronger interaction with polyvinylpyrrolidone. Therefore, in the preparation of dispersed silica, low molecular weight polyethylene glycol and zinc stearate are used. Zinc stearate can improve the dispersion ability of silica and, synergistically with silica, can improve the nucleation ability and grain refinement of polyester / polyamide. The low molecular weight polyethylene glycol on the silica surface enhances the binding effect between silica and pigment through the interaction with polyvinylpyrrolidone on the pigment surface, thereby stabilizing the pigment. The preparation method of composite zinc oxide involves mixing nano-zinc oxide with high molecular weight polyethylene glycol (PEG) and low molecular weight PEG, followed by ball milling and spray drying. Through ball milling, PEG and PEG are fixed on the surface of nano-zinc oxide. Nano-zinc oxide can improve the nucleation ability and grain refinement of polyester / polyamide, while PEG can improve softness. PEG can further form a connecting network within the fiber by interacting with polyvinylpyrrolidone on the pigment surface, thus fixing and stabilizing the pigment.
[0066] Based on the good pigment dispersibility of the masterbatches in Examples 1-12, and the advantages of high strength and color fastness, softness, dyeing performance and spinnability of the prepared microfibers, they have broad application prospects in suede fabrics for interior decoration of new energy vehicles.
Claims
1. A color masterbatch for microfiber, characterized in that, By weight, it consists of the following raw materials: 60-80 parts matrix resin, 20-40 parts pigment mixture, 3-3.5 parts dispersant, 0.3-0.5 parts composite zinc oxide, and 0.3-0.5 parts antioxidant; The pigment mixture is prepared by the following method: pigment is mixed with water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone, subjected to a first reflux stirring at 80-85°C, and spray-dried to obtain a dispersed pigment; silica is mixed with water, low molecular weight polyethylene glycol, and zinc stearate, subjected to a second reflux stirring at 85-90°C, and spray-dried to obtain dispersed silica; the dispersed pigment and dispersed silica are mixed and stirred at room temperature to obtain the pigment mixture. The composite zinc oxide is prepared by the following method: nano zinc oxide is mixed with water, high molecular weight polyethylene glycol and low molecular weight polyethylene glycol, ball-milled and spray-dried to obtain composite zinc oxide.
2. The masterbatch for microfiber according to claim 1, characterized in that, The matrix resin is polyester chips or polyamide chips; The intrinsic viscosity of the polyester chips is 0.5-1 dL / g; The intrinsic viscosity of the polyamide chips is 2-3 dL / g; The matrix resin is a dried matrix resin with a moisture content ≤100ppm. The dispersant is polyethylene wax; The antioxidant is one or a combination of antioxidant 1010, antioxidant 1076, and antioxidant 618.
3. The masterbatch for microfiber according to claim 1, characterized in that, In the preparation method of the pigment mixture, the particle size of the pigment is 10-20 nm; The mass ratio of pigment to water, high molecular weight polyethylene glycol, and polyvinylpyrrolidone is 100:500-600:5-6:5-6; The mass ratio of silica to water, low molecular weight polyethylene glycol, and zinc stearate is 100:500-600:5-6:5-6; The mass ratio of dispersed pigment to dispersed silica is 9-11:
1.
4. The masterbatch for microfiber according to claim 1, characterized in that, In the preparation method of the pigment mixture, when the first reflux stirring is carried out at 80-85℃, the stirring speed is 300-500 rpm and the stirring time is 60-90 min. During spray drying, the inlet air temperature is 170-190℃. When performing the second reflux stirring at 85-90℃, the stirring speed is 300-500 rpm and the stirring time is 90-120 min; When stirring at room temperature, the stirring speed is 300-500 rpm and the stirring time is 30-60 min.
5. The masterbatch for microfiber according to claim 1, characterized in that, In the preparation method of the pigment mixture, the pigment is one of carbon black, pigment red 214, pigment yellow 191, pigment purple 23, pigment blue 15:3, and pigment green 7; The high molecular weight polyethylene glycol has a molecular weight of 4000 or 6000; The polyvinylpyrrolidone is of type K30 or K60. The silica is hydrophilic fumed silica with an average primary particle size of 12 nm and a specific surface area of 200 m². 2 / g; The low molecular weight polyethylene glycol has a molecular weight of 400 or 600.
6. The masterbatch for microfiber according to claim 1, characterized in that, In the preparation method of the composite zinc oxide, the mass ratio of nano zinc oxide to water, high molecular weight polyethylene glycol, and low molecular weight polyethylene glycol is 100:400-450:5-6:5-6. During ball milling, use zirconia grinding balls with a particle size of 0.8-1.2mm, a ball-to-material ratio of 5-10:1, a ball milling speed of 900-1100rpm, and a ball milling time of 50-70min; During spray drying, the inlet air temperature is 170-190℃; The particle size of nano zinc oxide is 10-20 nm; The high molecular weight polyethylene glycol has a molecular weight of 4000 or 6000; The low molecular weight polyethylene glycol has a molecular weight of 400 or 600.
7. A method for preparing the color masterbatch according to any one of claims 1-6, characterized in that, Weigh the base resin, pigment mixture, dispersant, composite zinc oxide, and antioxidant according to the specified weight proportions, mix them at high speed, dry them, melt-extrude them, cool them, pelletize them, and dry them to obtain color masterbatch.
8. The method for preparing color masterbatch according to claim 7, characterized in that, During high-speed mixing, the high-speed mixing speed is 900-1100 rpm, and the high-speed mixing time is 10-20 min; The drying time is 10-20 minutes; During melt extrusion, the melting temperature is 260-285℃; During drying, the drying temperature is 110-120℃.
